Enhancing immunity prevents virus‐induced T‐cell‐mediated immunopathology in B cell‐deficient mice. Issue 5 (1st March 2019) - Straub, Tobias; Pircher, Hanspeter
Abstract: Hyper‐activated or deviated immune responses can result in immunopathological diseases. Paradoxically, immunodeficiency represents a frequent cause of such immune‐mediated pathologies. Immunopathological manifestations are commonly treated by immunosuppression, but in situations in which immunodeficiency is the basis of disease development, enhancing immunity may represent an alternative treatment option. Here, we tested this counterintuitive concept in a preclinical model using infection of mice with lymphocytic choriomeningitis virus (LCMV). Firstly, we demonstrate that infection of B‐cell‐deficient (B −/− ) but not of wild‐type (WT) mice with the LCMV strain Docile induced a rapid and fatal CD8 + T‐cell‐mediated immunopathological disease. Similar to WT mice, LCMV‐infected B −/− mice generated a potent, functional LCMV‐specific CD8 + T‐cell response but exhibited prolonged viral antigen presentation and increased vascular leakage in liver and lungs. Secondly, we were able to prevent this virus‐induced immunopathology in B −/− mice by active or passive T‐cell immunizations or by treatment with LCMV‐specific virus neutralizing or non‐neutralizing monoclonal antibodies (mAb). Thus, boosting antiviral immunity did not aggravate immunopathology in this model, but prevented it by decreasing the formation of target structures for damage‐causing CD8 + T cells. Abstract : Immunopathological diseases are usually treated by immunosuppression. Here, we show in B cell‐deficient mice that LCMV‐induced immunopathology can be prevented by enhancing antiviral immunity. These data support the concept that in situations where immunodeficiency is the cause of immunopathology, strengthening of immunity might represent an alternative treatment option.